Evaluation of genotoxic and antimicrobial effect induced by fungicide Dithane M-45 - ȘUŢAN, Nicoleta Anca; MAYASARI, Silviana; POPESCU, Aurel; TOMA, Adeline Mara; DELIU, Ionica (Studia Universitatis Babeș-Bolyai Biologia, 2015)
The cyto-genotoxic potential of fungicide Dithane M-45 on the root meristem cells of Tulipa praestans Hoog. cv. ‘Unicum’ and antimicrobial effects on some bacterial strains were investigated for concentrations lower than those currently used in agricultural practice. The results indicate a stimulating effect of the treatments with this fungicide on mitotic division, associated with a higher frequency of chromosomal aberrations for all concentrations tested, and for all root harvesting periods. The high sensitivity of root meristem cells of Tulipa praestans cv. ‘Unicum’ to the fungicide action suggest the potential of this species to be used as a plant-system for detecting the mutagenicity and genotoxicity, mainly the clastogenic and aneugenic effects, of various chemicals. However, only a slight antibacterial effect against the tested bacteria was observed in the paper disc and agar well diffusion assays.